Lymphocytes as internal standard in oxidative burst analysis by cytometry: A new data analysis approach - Peluso, Ilaria; Morabito, Giuseppa; Riondino, Silvia; La Farina, Francesca; Serafini, Mauro (Journal of immunological methods, 2012)
We propose a new data analysis approach for reactive oxygen species detection using Dihydrorhodamine123 in blood monocytes and neutrophils. This approach, based on data transformation using lymphocytes as internal standard, allows to appreciate free radical production by monocytes also without Phorbol 12-myristate 13-acetate (PMA) activation. In addition, this method is sensitive to differences in healthy subjects due to sub-pathological conditions, such as hypercholesterolemia.